PENGUSAHAAN HUTAN SECARA BERDAYA GUNA, BERHASIL GUNA, DAN BERDAYA SAING - Mis Joni; Anastasia Yunita; Rey Renaldi; Zelot Aritonang (Law Department, University of Widya Gama Mahakam Samarinda, 2024)
In carrying out forestry business activities, they should be carried out effectively, efficiently and under control, taking into account the principles of sustainable forest management and increasing their usability, results and competitiveness. One of the key aspects in achieving this is through implementing sustainable and sustainable forest management practices, by paying attention to and maintaining the ecological function of forests, and managing forest resources wisely. The effectiveness of implementing and controlling forestry business activities is also closely related to the government's role as a stakeholder in formulating policies that support sustainable forestry management practices and ensuring compliance with existing regulations. This research was conducted using normative research methods. The research results show that to achieve efficient, effective and competitive forest management, namely; Stakeholders must consistently encourage companies operating in the forestry sector to obtain sustainable forest management certification, such as a Forest Stewardship Council (FSC) certificate or the Program for the Endorsement of Forest Certification (PEFC), which can improve the company's image and open access to the market wider global.Companies must be able to obtain FSC and PEFC certificates as a reference that these companies have fulfilled all the elements of their commitment.